Broadband resonant calibration-free complex permittivity retrieval of liquid solutions. (September 2019) - Filonov, Dmitry S.; Kretov, Egor I.; Kurdjumov, Sergei A.; Ivanov, Viacheslav A.; Ginzburg, Pavel
Highlights: Material susceptibilities govern interactions between electromagnetic waves and matter and are of a crucial importance for basic understanding of natural phenomena and for tailoring practical applications. Here we present a new calibration-free method for relative complex permittivity retrieval, which allows using accessible and cheap apparatus and simplifies the measurement process. The method combines advantages of resonant and non-resonant techniques, allowing to extract parameters of liquids and solids in a broad frequency range. Abstract: Material susceptibilities govern interactions between electromagnetic waves and matter. They are of a crucial importance for basic understanding of natural phenomena and for tailoring practical applications. Here we present a new calibration-free method for relative complex permittivity retrieval, which allows use of inexpensive and accessible equipment, and simplifies the measurement process. This method combines the advantages of resonant and non-resonant techniques, which allow the extraction of material parameters of liquids and solids in a broad frequency range, where material's loss tangent is less than 0.5. The essence of the method is based on excitation of magnetic dipole resonance in a spherical sample with variable dimensions. The size-dependent resonant frequencies and the quality factors of magnetic dipolar modes are mapped on real and imaginary parts of permittivity by employing Mie theory. Samples are comprised of liquid solutions, enclosed in stretchable covers, which allows changing the dimensions continuously. This approach enables the tuning of the magnetic dipolar resonance over a wide frequency range, effectively making resonance retrieval method broadband. The technique can be extended to powders and solid materials, depending on their physical parameters, such as granularity and processability.